Cast versus wire fixation in displaced distal radius fractures in children : outcomes at skeletal maturity - Halim, Syurahbil Abdul (2019)
Introduction: Displacement following fracture reduction was a common complication during casting period in children previously treated for the distal radius fracture. Fracture stabilization with wire fixation was also used to maintain the reduction during fracture healing, but not without complications. We evaluated the clinical and radiological outcomes at skeletal maturity of distal radius fractures in children previously treated either with cast alone or with wire fixation. Methodology: A retrospective study of 57 patients with both metaphyseal and physeal fractures of distal radius was conducted. Out of 30 patients with metaphyseal fractures, 19 were in cast group and 11 were in wire group. Nineteen out of 27 patients with physeal fractures were from cast group while eight were from wire group. All were evaluated clinically and radiologically at or after skeletal maturity at the mean follow up of 6.5 years (3.0 to 9.0 years). Results: In metaphysis group, patients treated with wire fixation had more restriction in wrist palmarflexion (p=0.04) only but in physis group, more restriction of motion was found in both dorsiflexion (p=0.04) and palmarflexion (p=0.01) when compared to contralateral wrist. In physis group, there was a statistically significant difference in radial inclination (p=0.01) and dorsal tilt (p=0.03) between cast and wire fixation. No radiological difference was found in metaphysis group. All patients were pain free except one (5.3%) in physis group who had only a mild pain. Grip strength showed no statistical difference in all groups. Complications of wire included radial and ulnar physeal arrests, pin site infection and numbness. Conclusions: Cast and wire fixation showed excellent and good outcomes at skeletal maturity in children with previous distal radius fracture involving both metaphysis and physis. Site of fracture and type of treatment subjected have no influence on the grip strength at skeletal maturity.